The Supreme Court as a guarantor of ensuring the rights and freedoms of a person and a citizen - O. Artemenko; А. Yerosova (Law. Human. Environment)
The relevance of the chosen topic lies in the fact that Ukraine has been aligning its legislation with that of the European Union since 2022. As part of this process, further improvement of the Supreme Court’s activities is essential, as it serves as a guarantor of protecting the fundamental interests of every individual seeking judicial protection. The aim of the research is to review the processes of reforming the Supreme Court, taking into account the conducted Great Judicial Reform and the Eurointegration processes, as well as identifying proposals to increase public trust in the Supreme Court as the highest judicial body responsible for ensuring proper protection of rights and freedoms. The research methods used in the study include systemic- structural, comparative-legal, formal-legal, method of systematisation, as well as synthesis, analysis, and generalisation methods. The results of the study have shown that the Great Judicial Reform initiated in 2014 indicates that Ukraine is capable of considering European positive experience to enhance the overall compliance of Ukrainian legislation with European Union legislation while preserving its own age-old traditions in the field of justice and judiciary. It has been clarified that the key task of any transformations is to create conditions for the formation of an independent democratic rule of law state and all its branches of power – legislative, executive, and judicial. Thus, in a state aspiring to become legal, the court must be authoritative, independent, and should not be a bureaucratic institution but a real guarantor of citizens’ rights protection. It has been determined that the prerequisites for the implementation of the Great Judicial Reform were: low level of public trust in the judiciary as a whole, and the Supreme Court of Ukraine in particular, the presence of political-state influence on judges, and corrupt aspects. The materials of this work can be used for drafting legislative proposals in the field of the judicial system as a whole and its individual organs